The impact of heteropatriarchy and support on grief in sexual minorities: A qualitative study. - Olivas-González, Francisco Javier; Pérez-Marfil, María Nieves; Fernández-Alcántara, Manuel; Cruz-Quintana, Francisco (Death Studies, 2026)
Social support is a crucial element in the grieving process. However, in some social groups, such support may be absent or available only in a limited way. This would be the case for sexual minorities, who face prejudice, stigma, and rejection. The aim of this qualitative study is to explore the particularities of grief experienced by sexual minorities following the loss of a partner, using a Spanish sample. Individual semi-structured interviews were conducted with all participants. Qualitative results from 23 homosexual and bisexual people highlight the effects of heteropatriarchy on sexual minorities: gay men experience privileged status with visible partner relationships and widespread social support during grief, whereas lesbian women experience invisible relationships and instances of family and social rejection, leading to disenfranchized grief.